2011
DOI: 10.3389/fnhum.2011.00058
|View full text |Cite
|
Sign up to set email alerts
|

Obesity-Related Differences between Women and Men in Brain Structure and Goal-Directed Behavior

Abstract: Gender differences in the regulation of body-weight are well documented. Here, we assessed obesity-related influences of gender on brain structure as well as performance in the Iowa Gambling Task. This task requires evaluation of both immediate rewards and long-term outcomes and thus mirrors the trade-off between immediate reward from eating and the long-term effect of overeating on body-weight. In women, but not in men, we show that the preference for salient immediate rewards in the face of negative long-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
158
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(177 citation statements)
references
References 59 publications
16
158
3
Order By: Relevance
“…However, the neuroenergetic rigidity in obese individuals was accompanied by reduced gray matter volumes within frontotemporal brain structures, anterior cingulum, putamen, insula, and cerebellum compared with normal-weight control subjects, which is consistent with previous data providing evidence of obesity-related structural changes within the prefrontal cortex and the ventral striatum (19,20). Again, the question arises as to which mechanism might be behind the obesity-related brain morphology changes.…”
Section: Discussionsupporting
confidence: 89%
“…However, the neuroenergetic rigidity in obese individuals was accompanied by reduced gray matter volumes within frontotemporal brain structures, anterior cingulum, putamen, insula, and cerebellum compared with normal-weight control subjects, which is consistent with previous data providing evidence of obesity-related structural changes within the prefrontal cortex and the ventral striatum (19,20). Again, the question arises as to which mechanism might be behind the obesity-related brain morphology changes.…”
Section: Discussionsupporting
confidence: 89%
“…Obese women showed greater response to immediate reward (even in the face of delayed negative consequences) as opposed to lean women, and this differential response was not observed in obese men. 53 Another important imaging study demonstrated that youth who are at risk for obesity (defined as having both parents overweight/obese) showed an increased activation of the reward circuitry in response to food or monetary rewards, 54 suggesting that parental obesity can contribute to the child's risk for obesity. This same research group has also shown that reduced responding of the striatum to palatable food consumption can develop with weight gain, as opposed to existing prior to weight gain.…”
Section: Postnatal Effects Of a High-fat Dietmentioning
confidence: 99%
“…Furthermore, structural differences in NAcc volume have been positively associated with body mass index (BMI) in adults (5,6). Because the development of the NAcc precedes the development of prefrontal control systems (7), this structure is suggested to play a key role in motivating and establishing unhealthy eating behaviors early in the lifespan.…”
mentioning
confidence: 99%